Astaxanthin Suppresses PM2.5-Induced Neuroinflammation by Regulating Akt Phosphorylation in BV-2 Microglial Cells - Ryeong-Eun Kim (International Journal of Molecular Sciences, 2020)
Air pollution has become one of the most serious issues for human health and has been shown to be particularly concerning for neural and cognitive health. Recent studies suggest that fine particulate matter of less than 2.5 (PM2.5), common in air pollution, can reach the brain, potentially resulting in the development and acceleration of various neurological disorders including Alzheimer’s disease, Parkinson’s disease, and other forms of dementia, but the underlying pathological mechanisms are not clear. Astaxanthin is a red-colored phytonutrient carotenoid that has been known for anti-inflammatory and neuroprotective effects. In this study, we demonstrated that exposure to PM2.5 increases the neuroinflammation, the expression of proinflammatory M1, and disease-associated microglia (DAM) signature markers in microglial cells, and that treatment with astaxanthin can prevent the neurotoxic effects of this exposure through anti-inflammatory properties. Diesel particulate matter (Sigma-Aldrich) was used as a fine particulate matter 2.5 in the present study. Cultured rat glial cells and BV-2 microglial cells were treated with various concentrations of PM2.5, and then the expression of various inflammatory mediators and signaling pathways were measured using qRT-PCR and Western blot. Astaxanthin was then added and assayed as above to evaluate its effects on microglial changes, inflammation, and toxicity induced by PM2.5. PM2.5 increased the production of nitric oxide and reactive oxygen species and upregulated the transcription of various proinflammatory markers including Interleukin-1β (IL-1β), Interleukin-6 (IL-6), Tumor necrosis factor α (TNFα), inducible nitric oxide synthase (iNOS), triggering receptor expressed on myeloid cells 2 (TREM2), Toll-like receptor 2/4 (TLR2/4), and cyclooxygenase-2 (COX-2) in BV-2 microglial cells. However, the mRNA expression of IL-10 and arginase-1 decreased following PM2.5 treatment. PM2.5 treatment increased c-Jun N-terminal kinases (JNK) phosphorylation and decreased Akt phosphorylation. Astaxanthin attenuated these PM2.5-induced responses, reducing transcription of the proinflammatory markers iNOS and heme oxygenase-1 (HO-1), which prevented neuronal cell death. Our results indicate that PM2.5 exposure reformulates microglia via proinflammatory M1 and DAM phenotype, leading to neurotoxicity, and the fact that astaxanthin treatment can prevent neurotoxicity by inhibiting transition to the proinflammatory M1 and DAM phenotypes. These results demonstrate that PM2.5 exposure can induce brain damage through the change of proinflammatory M1 and DAM signatures in the microglial cells, as well as the fact that astaxanthin can have a potential beneficial effect on PM2.5 exposure of the brain.